Debridement and bone graft fusion via the lateral extracavitary approach combined with lateral and posterior screw-rod fixation in the treatment of thoracic spinal tuberculosis: A retrospective study of 38 cases - Shuanhu Lei; Jianwei Zhou; Li Guo; Xiaoli Guan; Mingtao Zhang; Haiyuan Yue; Xuewen Kang (Heliyon)
Objectives: Thoracic spinal tuberculosis (TB) is still common, and surgical treatment can rapidly relieve pain, correct deformity, reduce bone loss and prevent further damage to neurological function. We have practiced an efficient and safe surgical method. Methods: From January 2013 to April 2021, 38 patients with thoracic spinal TB were included in our study. Debridement and bone grafting were performed via the lateral extracavitary approach, combined with two different fixation methods. Data from these cases were analyzed retrospectively. Results: For all cases, the C-reactive protein (CRP) level and erythrocyte sedimentation rate (ESR) of all the patients decreased to normal levels at the last follow-up. The average visual analog scale (VAS) score was 7.5 ± 1.6 preoperatively and 0.6 ± 0.8 at the last follow-up, showing a significant reduction. The average angle of kyphosis correction was 6.3 ± 4.7°, and the loss of correction was 1.4 ± 1.6°. Neurological function was significantly improved in all cases according to the American Spinal Injury Association (ASIA) classification. Solid fusion was observed in all cases at the last follow-up. Conclusions: Debridement and bone graft fusion via the lateral extracavitary approach combined with two fixation methods can be very effective in the treatment of thoracic spinal TB.